Hizbut Tahrir Indonesia; Ekspresi Kebijakan dan Upaya Bertahan dalam Legislasi Perkawinan di Indonesia - Choiri, Muttaqin (Proceedings of Annual Conference for Muslim Scholars, 2019)
The study assensially gender equity in the Elementary curriculum that served as a basis for a proposed guide in preparing gender fair instructional materials. A descriptive analysis of Elementary Studies curriculum was the primary method used in this study. The participants’ perceptions on gender were compared and analyzed. Gender-fair education indicators served as criteria for comparison. The data gathered were processed qualitatively. The findings revealed that: (1) Indicators of gender biases in the learning environment were manifested in the learning environment, curriculum, and instructional processes; (2) Hidden curriculum plays an important role in informally transmitting values and attitudes in schools; (3) Leadership skill and tasks formerly given to male students were checked at present by female assertiveness; (4) Private and public school teachers and students differed in their perceptions on the learning environment; and (5) Gender-fair curriculum in Social Studies is a vital instrument in achieving equality, development, and peace